Odpowiedź :
Odpowiedź:
a)
5x + y = 4
x - 2y = 3
[tex]\left \{ {{y=4-5x} \atop {x-2(4-5x)=3}} \right.[/tex]
[tex]\left \{ {{y=4-5x} \atop {x-8+10x=3}} \right.[/tex]
[tex]\left \{ {{y=4-5x} \atop {11x=11/:11}} \right.[/tex]
[tex]\left \{ {{y=4-5*1} \atop {x=1}} \right.[/tex]
[tex]\left \{ {{y=4-5} \atop {x=1}} \right.[/tex]
[tex]\left \{ {{x=1} \atop {y=-1}}[/tex]
(x,y)=(1,-1)
b)
x = 4 + y
2x - 2y = 8
[tex]\left \{ {{x=4+y} \atop {2(4+y)-2y=8}} \right.[/tex]
[tex]\left \{ {{x=4+y} \atop {8+2y-2y=8}} \right.[/tex]
[tex]\left \{ {{x=4+y} \atop {0=0}} \right.[/tex]
(x,y)=(4+y,y)
y∈R
c)
x + y = 3
y = 3,5 - x
[tex]\left \{ {{x+3,5-x=3} \atop {y=3,5-x}} \right.[/tex]
[tex]\left \{ {{x-x=3-3,5} \atop {y=3,5-x}} \right.[/tex]
[tex]\left \{ {{0\neq0,5} \atop {y=3,5-x}} \right.[/tex]
(x,y)∈∅
Szczegółowe wyjaśnienie: